1990
DOI: 10.1055/s-2006-960984
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Activity of Tanzanian Medicinal Plants1

Abstract: Tanzanian medicinal plants were extracted and tested for in vitro antimalarial activity, using the multidrug resistant K1 strain of Plasmodium falciparum. Of 49 plants investigated, extracts of three plants were found to have an IC50 between 5-10 micrograms/ml, extracts of 18 other plants showed an IC50 between 10 and 50 micrograms/ml, all others were less active. The three most active extracts were obtained from the tubers of Cyperus rotundus L. (Cyperaceae), the rootbark of Hoslundia opposita Vahl. (Labiatae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
1
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(88 citation statements)
references
References 1 publication
1
84
1
2
Order By: Relevance
“…The antimalarial activities of a number of Tanzanian plants, many of which also occur in Kenya, have been reviewed by (17). Only 2 of 49 plants from that review (Gardenia jovis-tonantis and T. asiatica) were also used by the Kenyan Pokot herbalists.…”
Section: Discussionmentioning
confidence: 99%
“…The antimalarial activities of a number of Tanzanian plants, many of which also occur in Kenya, have been reviewed by (17). Only 2 of 49 plants from that review (Gardenia jovis-tonantis and T. asiatica) were also used by the Kenyan Pokot herbalists.…”
Section: Discussionmentioning
confidence: 99%
“…Clarkson et al (2004) reported that an extract of L. camara L. leaves demonstrated in vitro anti-plasmodial activity against a chloroquine-sensitive strain (D10) with an IC50 value of 11 µg/mL. The non-polar extract of root-bark also displayed high anti-malarial activity against the multidrug resistant K1 strain (Weenen et al, 1990). An ethanol extract of L. cujabensis Schauer showed lower activity when tested against chloroquine-resistant and chloroquine-sensitive strains of P. falciparum (IC50 14.7 µg/mL and 23.3 µg/ mL, respectively) (Desjardins, 1979).…”
Section: Anti-protozoal Activity (Anti-plasmodial Anti-malarial and mentioning
confidence: 99%
“…The naphthoquinones [3] in the roots and stem bark of K. africana possess anti-trypanosomal [4] and anti-microbial activities [5] and are cytotoxic against melanoma and renal carcinoma cells [6]. The aqueous extract of its leaves and fruits was found to have anti-diarrhoeal, antileprotic, anti-malarial, and anti-implantation activities [7]. The whole plant is accounted for its analgesic, anti-inflammatory, anti-molluscidal and antioxidative properties [8,9].…”
Section: Introductionmentioning
confidence: 99%